Sustained exendin-4 secretion through gene therapy targeting salivary glands in two different rodent models of obesity/type 2 diabetes. - Giovanni Di Pasquale (Public Library of Science (PLoS), 2012)
Exendin-4 (Ex-4) is a Glucagon-like peptide 1 (GLP-1) receptor agonist approved for the treatment of Type 2 Diabetes (T2DM), which requires daily subcutaneous administration. In T2DM patients, GLP-1 administration is reported to reduce glycaemia and HbA1c in association with a modest, but significant weight loss. The aim of present study was to characterize the site-specific profile and metabolic effects of Ex-4 levels expressed from salivary glands (SG) in vivo, following adeno-associated virus-mediated (AAV) gene therapy in two different animal models of obesity prone to impaired glucose tolerance and T2DM, specifically, Zucker fa/fa rats and high fed diet (HFD) mice. Following percutaneous injection of AAV5 into the salivary glands, biologically active Ex-4 was detected in the blood of both animal models and expression persisted in salivary gland ductal cell until the end of the study. In treated mice, Ex-4 levels averaged 138.9±42.3 pmol/L on week 6 and in treated rats, mean circulating Ex-4 levels were 238.2±72 pmol/L on week 4 and continued to increase through week 8. Expression of Ex-4 resulted in a significant decreased weight gain in both mice and rats, significant improvement in glycemic control and/or insulin sensitivity as well as visceral adipose tissue adipokine profile. In conclusion, these results suggest that sustained site-specific expression of Ex-4 following AAV5-mediated gene therapy is feasible and may be useful in the treatment of obesity as well as trigger improved metabolic profile.